THE PROBLEM OF DEFINING A FAMILY CHRONICLE AS A LITERARY GENRE IN ENGLISH LITERARY CRITICISM - Lokteva, Nadezhda; Balich, Dilyara (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
This article discusses the problems of defining the genre of family chronicles in English-language literary criticism of the XIX–XX centuries. The assessment of the family chronicle genre in English literary criticism shows that the author, who deals with the family chronicle genre, tells not only about the life of one or several generations, but also the social and historical life of the nation. In the family chronicle, the whole is given through the part, which shows that any family depicted in the work is an exact reproduction of the whole society in miniature. In this regard, the studied genre is a peculiar form of a story about the life of a particular society. In American literature, the first examples of the family chronicle genre date back to the second half of the XIX century, which shows that the genre appears in American literature almost at the same time with European literature. It is noted that from the very beginning the writers Fenimore Cooper, Louisa May Alcott and Cable created their original works before the classical European versions (Thomas Mann, Martin du Gard, John Galsworthy).